Waist circumference and waist:height ratio percentiles using LMS method in Chilean population - Lopez-Legarrea, P.; Garcia-Rubio, J.; Oviedo-Silva, F.; Collado-Mateo, D.; Merellano-Navarro, E.; Olivares, P.R. (Nutrition, metabolism, and cardiovascular diseases, 2017)
The concern over the weight gain problem continues to grow among both the international scientific community and public health authorities, since overweight and obesity prevalence rates continue to increase worldwide. In Chile, two out of three people are overweight, whereas 25% of the adult population is obese. Abdominal fat, has been linked to the development of a number of metabolic disorders. Waist circumference (WC) and the waist:height ratio (WHtR) have recently been evidenced as good predictors of metabolic risk for both adults and children. Thus, the present work aims at establishing smoothed centile charts and LMS tables for WC and WHtR for Chilean adults based on data from the National Health Survey-ENS, in order to have reliable information for identifying groups at risk. A sample of 4788 subjects aged 15–75 years old (mean age 46 ± 18 years old) was considered. Body weight, height, and WC were measured and Body Mass Index (BMI) and WHtR were also determined. Percentiles were calculated using the L (curve Box–Cox), M (curve median), S (curve coefficient of variation) method. In the obese group the WC cutoff values were 99.75 cm and 92.35 cm for men and women, respectively. The cutoff point for WHtR was 0.59 for both obese men and women. The study shows, for the first time, reference values for WC and WHtR for Chilean adults. •In Chile, two out of three people are overweight, 25% of adults are obese.•The study shows reference values for WC and WHtR for first time in Chile.•A sample of 4788 subjects aged 15–75 (mean age 46 ± 18 years old) was considered.•WHtR has recently been evidenced as a good predictor of metabolic risk.